Influência das normas internacionais na produção leiteira brasileira: um olhar crítico sobre as boas práticas de produção para a agricultura familiar na Amazônia - Corrêa, Cristiane Fonseca Costa (2016)
Structural changes imposed on Brazil’s dairy industry are influenced by the international market while it presses local industries and local producers. One of the main difficulties in the dairy sector is the standardization of milk based on the international standards of quality. So, to meet these requirements, standard operating procedures are established for the entire production chain, and they’re called '' Good dairy farming practices”. This paper addresses in a systemic way the influences of these standards in the Brazilian milk production, and the difficulties for adopting these procedure standards in family farming, especially in the Amazon region. The Amazonian family farmer is characterized by a peculiar diversity related to the ways they produce and live in society. In addition, there is at the same time a variety of local contexts very striking in the Amazon, which involve and influence the practices of farmers, making it difficult to join a homogenizing principle of good practices. The criticism of this paper does not report the need for sanitation improvements in milk production practices, but it wants to demonstrate as a leading line that the local context and the logic of producers are extremely necessary, so that the actions elaborated can value their practices and have them as a starting point. It should be noted in this study that the result of standard procedures for family farmers is the differentiation and social reunification in between them, where some are consolidated in milk production and others are excluded.